General John A. Rawlins : no ordinary man - Ottens, Allen J. (Indiana University Press, 2021)
"No one succeeds alone, and Ulysses S. Grant was no exception. From the earliest days of the Civil War to the heights of Grant's power in the White House, John A. Rawlins was ever at Grant's side. Yet Rawlins's role in Grant's career is often overlooked, and he barely received mention in Grant's own two-volume Memoirs. General John A. Rawlins: No Ordinary Man by Allen J. Ottens is the first major biography of Rawlins in over a century and traces his rise to assistant adjutant general and ultimately Grant's secretary of war. Ottens presents the portrait of a man who teamed with Grant, who submerged his needs and ambition in the service of Grant, and who at times served as the doubter who questioned whether Grant possessed the background to tackle the great responsibilities of the job. Rawlins played a pivotal role in Grant's relatively small staff, acting as administrator, counselor, and defender of Grant's burgeoning popularity. Rawlins qualifies as a true patriot, a man devoted to the Union and devoted to Grant. His is the story of a man who persevered in wartime and during the tumultuous years of Reconstruction and who, despite a ravaging disease that would cut short his blossoming career, grew to become a proponent of the personal and citizenship rights of those formerly enslaved. General John A. Rawlins will prove to be a fascinating and essential read for all who have an interest in leadership, the Civil War, or Ulysses S. Grant"--